2018
DOI: 10.1080/13561820.2018.1514373
|View full text |Cite
|
Sign up to set email alerts
|

Are interprofessional healthcare teams meeting patient expectations? An exploration of the perceptions of patients and informal caregivers

Abstract: Poor teamwork skills in healthcare have been found to be a contributing cause of negative incidents in patient care, whilst effective teamwork has been linked to more positive patient outcomes. The aim of this research is to explore views of patients and informal caregivers on the key characteristics of effective healthcare teams and their experiences of healthcare teams using a qualitative approach. A focus group schedule was developed from existing literature to explore this. Topics included the purpose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…Moreover, Tractenberg et al [ 34 ] concluded that there are qualitative differences in therapy outcomes that are using a patient-centered approach. Cutler et al [ 35 ] summed up that including the patient in the health care professionals team makes sense for long-lasting treatments such as physiotherapy or mental health services but less for acute treatment like emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tractenberg et al [ 34 ] concluded that there are qualitative differences in therapy outcomes that are using a patient-centered approach. Cutler et al [ 35 ] summed up that including the patient in the health care professionals team makes sense for long-lasting treatments such as physiotherapy or mental health services but less for acute treatment like emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…There are assumptions that the frequency with which, for example, certain professions are presented in social media is responsible for stereotyping (Gorham, 1999). In a recent qualitative study, patients felt healthcare professionals usually introduced themselves as individuals rather than members of the healthcare team (Cutler et al, 2019). This could be attributed to the fact is that certain healthcare professionals do not feel they are a contributing member to the healthcare team (Delva et al, 2008).…”
Section: "Feeling Of Exclusion"mentioning
confidence: 99%
“…Patient satisfaction has been linked with team-based care (Will et al, 2019), however patients' knowledge of the healthcare team is not always reflective of the diverse professions involved in their care (Parsons et al, 2016). Public perceptions of interprofessional teams and the attributes needed for their effectiveness seem to be underrepresented in the literature (Cutler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of the patient or the patient's representative as a key team member has been identified as a quality of a good team and impacts on patient care. In order to facilitate patient engagement and work in partnership with patients, there needs to be trust and transparency between healthcare professionals and patients 6 .…”
Section: Mr Editormentioning
confidence: 99%